Kontribusi Hasil Belajar, Kecerdasan Emosi, dan Motivasi Kerja Terhadap Kinerja Lulusan D-III Keperawatan - Ni Luh Putu Yuni Suntari; I Wayan Sukawana; I Made Oka Bagiarta (Jurnal Gema Keperawatan, 2013)
This research aim to know about the contribution of the study result, emotional question and job motivation factor toward the work performance of the graduated third diploma of nursing at Poltekkes Kemenkes Denpasar, who works in Sanglah General Hospital period of 2012. This is application research which applied the ex post facto, with correlational design. The research sample are 135 nurse. The result show that: 21,1% contribution of result study for work performance. Have 14,8% contribution of emotional question for work performance, and 33,2% contribution of job motivation factor for work performance. 21,3% contribution together between study result, emotional question, and job motivation for work performance.